Amperometric Biosensors for Lactate, Alcohols, and Glycerol Assays in Clinical Diagnostics - Smutok, Oleh; Gayda, Galina; Dmytruk, Kostyantyn; Klepach, Halyna; Nisnevitch, Marina; Sibirny, Andriy; Puchalski, Czesław; Broda, Daniel; Schuhmann, Wolfgang; Gonchar, Mykhailo; Sibirny, Vladimir (IntechOpen, 2011)
None